[OP.8D.06] OCULAR FUNDUS PHOTOGRAPHY WITH A SMARTPHONE DEVICE IN ACUTE HYPERTENSION. (September 2016) - Muiesan, M.L.; Riviera, M.; Pintossi, C.; Bertacchini, F.; Colonetti, E.; Salvetti, M.; Paini, A.; Poli, M.; Semeraro, F.; Rosei, E. Agabiti; Russo, A.
Abstract : Objective: The ocular fundus (FO) examination is infrequently and poorly performed in the emergency department (ED) clinical settings, placing patients at risk for missed diagnosis of hypertensive emergencies. Aim: to investigate the feasibility of the FO photography with a smartphone small optical device (D-Eye; J Ophtalmol. 2015) in a ED setting and to compare it to a traditional FO examination. Design and method: The study included 41 consecutive patients (mean age 69 ± 16 years, 50% women) presenting to an hospital ED with an acute increase in blood pressure (SBP >180 and/or DBP >100 mmHg). When admitted to the ED all patients had mydriatic FO examination obtained by an Emergency physician (EP) using both a traditional ophtalmoscope and a commercially available FO smartphone device (D-Eye, Si14 S.p.A., Padova). All FO images and videos recorded with the D-Eye system were analysed by 2 independent expert (ophthalmologist) and inexpert (EP) observers. A quantitative score of hemorrages, exudates and/or papillary edema was used (0 absent, 1 early, 2 moderate, 3 severe, 4 very severe). The Cohen K coefficient (Ki) was used to assess the inter-observer concordance index. Results: Six patients had headache, 6 had focal neurologic symptoms, and 4 had acute visual changes. The mean duration of FO examination was 130 ± 39 and 74 ± 31 seconds for traditional ophtalmoscopy and for smartphone D-Eye, respectively. No relevant abnormalities of their FO were detected by traditional ophthalmoscopy, performed by the EP, while a signifcant number of abnormal FO findings were detected by the use of the D-eye device in 17 and 19 patients by the EP and ophthalmologist, respectively. The Ki value ranged from 0, 66 to 0, 77 (good concordance) for the assessment of hemorrages and exudates, and from 0, 89 to 0, 90 (optimal concordance) for the evaluation of presence and severity of papilledema. Conclusions: Our results show that a new small smartphone device (D-Eye) may be feasible in an ED setting for the fundoscopic examination, detecting a signifcant number of abnormal FO. The reliability of relevant FO abnormalities seems to be superior in respect to traditional fundoscopy.